Unveiling a promising active host material for sodium metal anodes through V2AlC max derivation - Wasnik, Kundan; Patrike, Apurva; Shelke, Manjusha V. (ACS Applied Energy Materials, 2024)
To address the issue of nonuniform sodium deposition, in this study, V2ZnC (named VZC), which is synthesized by substituting Zn for Al in V2AlC, is used as a host material to facilitate effective Na utilization. The key concept is to utilize Zn and its forms as an active site to trap Na, while the high mechanical strength of VZC can accommodate volume changes in the sodium metal anode during charging and discharging. VZC displayed regulated plating and stripping at a higher current and capacity of 8 mA cm-2 and 2 mAh cm(-2), respectively, with Coulombic efficiency close to 99.99%.
Keywords: electrodes; Nucleation; overpotential; sodium metal; XPS depth profiling